Algorithms for calculating the leading quantum electrodynamics P(1/r3) correction with all-electron molecular explicitly correlated Gaussians. (22nd February 2017) - Stanke, Monika; Jurkowski, Jacek; Adamowicz, Ludwik
Abstract: Algorithms for calculating the quantum electrodynamics Araki–Sucher correction for n -electron explicitly correlated molecular Gaussian functions with shifted centers are derived and implemented. The algorithms are tested in calculations concerning the H2 molecule and applied in ground-state calculations of LiH and H 3 + molecules. The implementation will significantly increase the accuracy of the calculations of potential energy surfaces of small diatomic and triatomic molecules and their rovibrational spectra.